Pengaruh Pembelajaran Memanfaatkan Modul Tanaman Obat Tradisional Berbantuan Game Edukasi Wayground untuk Meningkatkan Nilai Formatif Siswa SMA - Rezky Aulianur Syahbana; Kurnia Dewi; Erni Yaya; Senopi Senopi; Ernawati Ernawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Biology is one of the general subjects taught to all students in grade 10 and continues in higher grades for students who choose science-related (MIPA) specialization. Biology learning in senior high schools is often considered less engaging when it relies solely on textbooks as learning resources, due to limited information and a lack of connection to everyday life. One effort to address this issue is through the use of contextual learning modules and interactive learning media. In this regard, biology learning modules can incorporate the utilization of traditional medicinal plants as solutions for maintaining health and treating diseases. Traditional medicinal plants are highly relevant to biodiversity topics due to the abundance of genetic resources and the extensive ancestral knowledge related to medicinal plants. This study aims to determine the effect of learning that utilizes a traditional medicinal plant module assisted by the Wayground educational game on improving senior high school students’ formative assessment scores. The Wayground educational game is used to increase student engagement through features that support independent learning and repeated practice, allowing students to learn from their mistakes. The results show an improvement in students’ formative scores, indicated by an increase in the percentage of correct answers on Wayground quizzes from 48% to 72%, as well as an increase in the percentage of students who completed the quizzes from 78% to 92%. Based on these findings, it can be concluded that biology learning utilizing a traditional medicinal plant module assisted by the Wayground educational game has a positive effect on improving senior high school students’ formative assessment scores.